2018
DOI: 10.1002/adsc.201701475
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)‐Schiff Base Complex‐Functionalized Polyacrylonitrile Fiber as a Green Efficient Heterogeneous Catalyst for One‐Pot Multicomponent Syntheses of 1,2,3‐Triazoles and Propargylamines

Abstract: A series of copper(II)‐Schiff bases‐functionalized polyacrylonitrile fiber catalysts were successfully prepared using copper acetate as copper source and characterized by elemental analysis, fourier‐transfer infrared spectroscopy, ultraviolet‐visible spectroscopy, X‐ray photoelectron spectroscopy and inductively coupled plasma analysis. Excellent physical strength and thermal stability of the fiber catalysts were demonstrated by scanning electron microscopy, X‐ray diffraction, thermogravimetric/differential sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…This indicates that the coordination of Co 2+ and Ni 2+ metal ions to –NH 2 group could not change the oxidation states due to less coordination tendency of –NH 2 group. However, the Cu‐MOF exhibits the peaks for both Cu 2+ (955.34 and 935.06 eV) and Cu + (952.82 and 933.01 eV) oxidation states . The existence of both +2 and +1 states can be ascribed to: i) the effective coordination of –NH 2 group through non‐bonded electrons of nitrogen and ii) the formation oxide layer on Ti‐MOF surface, which further confirms the existence of CuO x after the coordination as supported by XRD analysis.…”
Section: Resultssupporting
confidence: 58%
“…This indicates that the coordination of Co 2+ and Ni 2+ metal ions to –NH 2 group could not change the oxidation states due to less coordination tendency of –NH 2 group. However, the Cu‐MOF exhibits the peaks for both Cu 2+ (955.34 and 935.06 eV) and Cu + (952.82 and 933.01 eV) oxidation states . The existence of both +2 and +1 states can be ascribed to: i) the effective coordination of –NH 2 group through non‐bonded electrons of nitrogen and ii) the formation oxide layer on Ti‐MOF surface, which further confirms the existence of CuO x after the coordination as supported by XRD analysis.…”
Section: Resultssupporting
confidence: 58%
“…260 The potential of multicomponent reactions for the preparation of 1H-1,2,3-triazole derivatives has become extremely useful in recent years to produce complex macromolecular structures 261 and several studies have reported the use of this strategy in the preparation of 1,4-disubstituted 1H-1,2,3-triazoles. [262][263][264][265][266][267]…”
Section: Scheme 25mentioning
confidence: 99%
“…To perform the A 3 coupling effectively, the selective and active catalysts are required. Numerous catalytic systems have been explored in the A 3 coupling till now [30][31][32][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Among them copper, silver and gold catalysts seem to play the most vital role in promoting these transformations [30,32,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…To perform the heterogenization of catalytically active species both synthetic (e.g. polyacrylonitrile fibers, polystyrene resins) [56][57][58] and natural organic polymers (e.g. chitosan) might be used [59,60].…”
Section: Introductionmentioning
confidence: 99%